2014
DOI: 10.48550/arxiv.1403.1515
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linear Recognition of Almost Interval Graphs

Abstract: Let interval + kv, interval + ke, and interval − ke denote the classes of graphs that can be obtained from some interval graph by adding k vertices, adding k edges, and deleting k edges, respectively. When k is small, these graph classes are called almost interval graphs. They are well motivated from computational biology, where the data ought to be represented by an interval graph while we can only expect an almost interval graph for the best. For any fixed k, we give linear-time algorithms for recognizing al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…The fixed-parameter tractability of their completion versions were shown by Kaplan et al [13] and Villanger et al [26]; their vertex deletion versions were shown by van 't Hof and Villanger [25] and Cao and Marx [7]. A very recent result of Cao [5] complemented them by showing that the edge deletion versions are FPT as well.…”
Section: Discussionmentioning
confidence: 94%
“…The fixed-parameter tractability of their completion versions were shown by Kaplan et al [13] and Villanger et al [26]; their vertex deletion versions were shown by van 't Hof and Villanger [25] and Cao and Marx [7]. A very recent result of Cao [5] complemented them by showing that the edge deletion versions are FPT as well.…”
Section: Discussionmentioning
confidence: 94%
“…Recall that Lin et al [10] have given a linear-time algorithm for verifying whether a circular-arc model is normal and Helly. In fact, given a circular-arc model, we can in linear time find the minimum number of arcs that cover the circle [2]. Proof of Theorem 1.3.…”
Section: Theorem 27 If (G) Is An Interval Graph Then We Can In O(n + ...mentioning
confidence: 94%
“…The crucial idea behind our certifying algorithm is a novel correlation between normal Helly circular-arc graphs and interval graphs, which can be efficiently used for algorithmic purpose. This was originally proposed in the detection of small forbidden induced subgraph of interval graphs [2], i.e., the opposite direction of the current paper. In particular, in [2] we have used a similar definition of the auxiliary graph and pertinent observations.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations